Genetic testing for hereditary cancer syndromes: patient recommendations for improved risk communication. (27th April 2020) - Pollard, Samantha; Kalloger, Steve; Weymann, Deirdre; Sun, Sophie; Nuk, Jennifer; Schrader, Kasmintan A.; Regier, Dean A.
Abstract: Background: Multi‐gene panel testing is replacing single‐gene testing for patients with suspected hereditary cancer syndromes. The detection of a hereditary cancer syndrome allows tested individuals to initiate enhanced primary and secondary prevention efforts—where available—with a view to reduce disease burden. Current policy prevents testing programmes from communicating genetic test results with potentially affected family members, yet it is well documented that tested individuals face multiple challenges in initiating such discussions with relatives. Objective: In response to this challenge, we sought patient recommendations about how to improve genetic risk communication to enhance interfamilial discussions about primary and secondary disease prevention. Design: We conducted 25 semi‐structured interviews with individuals who received genetic testing through British Columbia's Hereditary Cancer Program between 2017 and 2018. Interviews were professionally transcribed and analysed using a constant comparative approach. Results: Participants described difficulty engaging in conversations with relatives who were resistant to receiving genetic risk information, when communicating with younger relatives and where participants reported strained familial relationships. Participants recommended that testing facilities provide a summary of results and implications and that resources be made available to prepare patients for challenging discussions with family members. Discussion: Our study demonstrates that individuals undergoing genetic testing for suspected hereditary cancer syndromes would benefit from additional supportive resources alongside genetic counselling. Providing this on‐going support will enhance the accurate and transparent communication of risk to facilitate the uptake of cascade testing and enhanced prevention strategies.